2022
DOI: 10.1002/adma.202201801
|View full text |Cite
|
Sign up to set email alerts
|

A Dendrite‐Free Lithium‐Metal Anode Enabled by Designed Ultrathin MgF2 Nanosheets Encapsulated Inside Nitrogen‐Doped Graphene‐Like Hollow Nanospheres

Abstract: generated on the anode surface breaks fragilely, bringing about further electrolyte decomposition and causing low coulombic efficiency (CE) and rapid capacity fade. [4] For decades, extensive endeavors have been made to overcome these issues by developing functional electrolytes, [5][6][7] constructing artificial SEI films, [8][9][10][11] and engineering well-designed host materials. [12][13][14][15][16][17] Among various strategies, the host materials have gained considerable interest because they are effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 35 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…The synthesis of graphene materials and graphene-based composites has been involved in considerable strategies for energybased applications. Owing to the large flat layered structure with strong sp 2 covalent bonds, high surface area, and excellent electron transport properties, graphene sheets are considered to be a promising electrode material for energy devices such as lithium batteries, supercapacitors, and many others [11,12]. Graphene has a high theoretical surface area value of 2630 m 2 g -1 [13], and it possesses unique physicochemical properties like superior electrical conductivity, excellent 3 chemical stability, and good thermal conductivity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of graphene materials and graphene-based composites has been involved in considerable strategies for energybased applications. Owing to the large flat layered structure with strong sp 2 covalent bonds, high surface area, and excellent electron transport properties, graphene sheets are considered to be a promising electrode material for energy devices such as lithium batteries, supercapacitors, and many others [11,12]. Graphene has a high theoretical surface area value of 2630 m 2 g -1 [13], and it possesses unique physicochemical properties like superior electrical conductivity, excellent 3 chemical stability, and good thermal conductivity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the XPS results show that there are CO, C–O groups in the ERGO@Cu/PA mesh, with an obvious oxygen doping level. Mukherjee et al and Wang et al , systematically studied the role of structural defects and oxygen-containing groups in the graphene lattice in inducing Li deposition through theoretical calculation and experimental characterization. It is found that Li is preferentially adsorbed to these topological defects in a stable form and acts as a nucleation site for further deposition to induce uniform deposition of Li.…”
Section: Resultsmentioning
confidence: 99%
“…For the bottleneck of uncontrollable Li dendrite, several different strategies were used to suppress dendrite growth and enhance the cycling stability, modifying a strong artificial SEI film on the Li interface as a blocking layer for dendritic growth, or homogenizing the electric field distributions on an anode interface during Li deposition through modification of the electrolyte or the introduction of additives, as well as reducing the Li nucleation overpotential and homogenize Li deposition by employing lithiophilic materials. Besides, the 3D Cu current collector can inhibit the growth of Li dendrite and effectively alleviate the volume expansion through the combination with Li metal (electrodeposition, melting, and rolling), which improves the cycling stability of the Li metal battery, as well as decreases the excessive use of Li foil to a proper extent, reducing the production cost and security risks.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and the porous structure with pore size of COF can be adjusted by selecting the assembled monomers with desired length and geometry at the molecular level. Recently, many reports on the application of COF in photocatalysis, [16,17] CO 2 adsorption, [18] electrochemical energy storage [19][20][21][22][23][24][25] and other fields [26,27] have been reported. It is worth noting that the π-electron delocalization of π-orbital overlap and the maximum energy induced from the van der Waals interaction result in the high specific surface area and high porosity of COF materials, leading to more accessible active sites for energy-storage reactions.…”
Section: Introductionmentioning
confidence: 99%